2021
DOI: 10.37715/jtce.v1i1.1797
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Technology Acceptance Model (Tam) and Brand Trust Toward Consumer’s Intention to Buy in TIKET.COM With E-Wom as a Moderating Variable

Abstract: The growing number of online travel agent in Indonesia, pushed tiket.com to compete in increasing its application brand performance and consumer’s perception. This research uses a quantitative method to test the hypothesis regarding Technology Acceptance Model and Brand Trust with E-WOM as a moderating variable. The population of this research is Indonesian consumer that had ever want or made a purchase in tiket.com. The sampling technique used in this research is non-probability sampling method with 110 as it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…value of 0.014, which is smaller than 0.05. Therefore, it can be concluded that TAM significantly affects consumers' intention to make purchases on tiket.com [24]. This research supports the selection of TAM as an approach to understanding consumer interest in purchasing tickets.…”
Section: Previous Studiessupporting
confidence: 68%
“…value of 0.014, which is smaller than 0.05. Therefore, it can be concluded that TAM significantly affects consumers' intention to make purchases on tiket.com [24]. This research supports the selection of TAM as an approach to understanding consumer interest in purchasing tickets.…”
Section: Previous Studiessupporting
confidence: 68%
“…In this context, TAM refers to the Technology Adoption Model. Which Lederer et al in Wijaya & Susilo (2021) TAM imply that convenience and utility forecast the app's adoption and use. The degree to which a user embraces and makes effective use of a given technology is often evaluated using this paradigm.…”
mentioning
confidence: 99%
“…The degree to which a user embraces and makes effective use of a given technology is often evaluated using this paradigm. Indicators of perceived usefulness and perceived simplicity of use are the building blocks of the Technology Acceptance Model, as described by Pavlou in Wijaya & Susilo (2021). In this context, "how far someone believes in using the system to improve his or her productivity in working" is an acceptable working definition of "perceive usefulness" (PU).…”
mentioning
confidence: 99%